Pengaruh Pengangguran, Upah Minimum, Dan PDRB Terhadap Kemiskinan Di Provinsi Jawa Timur - Regina Kezia Rahayu Syahputri; Ladi Wajuba Perdini Fisabilillah (Universitas Negeri Surabaya, 2022)
Poverty is a fundamental problem that continues to be a priority and needs to be solved. This study aims to analyze the effect of unemployment, minimum wage, and gross regional domestic product on poverty in East Java Province. This study uses secondary data which obtained from Central Bureau of Statistics in East Java Province and the decree of governor in East Java Province for period 2018-2021. The research method is quantitative and analyzed with panel data regression with Fixed Effect Model. The results of this study show that unemployment and minimum wage have significant and positive effect on poverty in East Java Province. Meanwhile, gross regional domestic product has significant and negative effect on poverty in East Java Province. Also, unemployment, minimum wage, and gross regional domestic product have simultaneously effect on poverty in East Java Province.